2022
DOI: 10.14740/jh977
|View full text |Cite
|
Sign up to set email alerts
|

Hematological, Biochemical Properties, and Clinical Correlates of Hemoglobin S Variant Disorder: A New Insight Into Sickle Cell Trait

Abstract: Background The sickle cell trait (SCT) disorder possesses a clinical heterogeneity ranging from a symptomless condition to sudden death. This study aimed to develop a diagnostic approach that helps the characterization and identification of SCT from normal subjects and sickle cell disease (SCD) patients, and to assess its severity. Methods Sixty controls, 24 SCD patients and 31 SCT subjects were assessed clinically, radiologically and by laboratory investigations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…In the current study, we found significantly lower Hb, PCV, and MCHC and higher reticulocytes in SCA patients than in SCT patients. Our findings were in agreement with other studies [19]. Also, we found higher MCHC in SCT patients compared to SCD patients, while MCHC was low in SCD patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, we found significantly lower Hb, PCV, and MCHC and higher reticulocytes in SCA patients than in SCT patients. Our findings were in agreement with other studies [19]. Also, we found higher MCHC in SCT patients compared to SCD patients, while MCHC was low in SCD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Also, non-significant differences were obtained in age, gender, leukocytes, platelets, MCV, MCH, MCHC, and G6PD between SCD patients and controls (P ˃ 0.05). Similar results were obtained in other studies by comparing SCA patients with controls [19]. Khaled et al, (2022) found significantly lower levels of Hb, PCV, RBC, MCV, and MCH and higher levels of reticulocytes in SCD patients than controls, as well as non-significant differences in age, gender, WBC, platelets, and MCHC [19].…”
Section: Discussionsupporting
confidence: 85%
“…The percentage of HbS, which ranges from 25% to 45% [50], may affect the hematological and clinical characteristics of SCT, including ERM [51]. However, the Kennedy et al study suggested that HbS levels in SCT were very unlikely to have any clinical significance [52].…”
Section: Discussionmentioning
confidence: 99%